The Vigilance Promoting Drug Modafinil Modulates Serotonin Transmission in the Rat Prefrontal Cortex and Dorsal Raphe Nucleus. Possible Relevance for Its Postulated Antidepressant Activity - Ferraro, Luca; Antonelli, Tiziana; Beggiato, Sarah; Cristina Tomasini, Maria; Fuxe, Kjell; Tanganelli, Sergio (Mini Reviews in Medicinal Chemistry, 2013)
Modafinil, (RS)-2-(diphenylmethylsulfinyl)acetamide derivative (Modiodal, Provigil), is a vigilance-promoting agent which reduces sleep episodes by improving wakefulness. It is approved by the USA FDA for narcolepsy, shiftwork sleep disorder and obstructive sleep apnoea with residual excessive sleepiness despite optimal use of continuous positive airway pressure. Unlike classical psychostimulants such as amphetamine and amphetamine-like compounds, the awaking effect of modafinil is not associated with a disturbance of nighttime sleep, tolerance, and sensitization. Its precise mechanism of action is still unclear. In animal studies, modafinil and its analogues have been shown to modify dopaminergic, noradrenergic, glutamatergic, GABAergic, serotoninergic, orexinergic, and histaminergic pathways. Besides the approved use in sleep disorders, modafinil has been investigated for the treatment of fatigue, impaired cognition and some symptoms in a number of other disorders. In particular, clinical studies seem to indicate that the drug could be particularly successful in the treatment of depression and its use in major depressive and bipolar disorders, has been suggested. However, the molecular mechanisms underlying this possible effect are still unknown. The present review firstly summarizes the structure-activity relationship studies and the mechanism of action of modafinil and its related compounds. Then, it focuses on data demonstrating that modafinil interacts with serotonin neuronal activity in rat frontal cortex and dorsal raphe nucleus, two brain areas linked together and involved in depression. Preclinical and clinical evidence of a positive interaction between modafinil and classical antidepressant drugs, is also summarized.
Keywords: dorsal raphe nucleus and hippocampus